A súmula com efeito vinculante no direito tributário - Pimenta, Marcos Rogério Lyrio (2009)
The present work intends to study some issues of the binding judicial precedent in the brazilian tax law. So, we will investigate some categories of the General Theory of Law, especially examining the legal rules and the sources of law, due to its relation with the object of this study. Then, we will analyze the structure of the Anglo-Saxon law model (common law) and the codified law model (civil law); the binding judicial precedent evolution in the brazilian legal system until the nº 45/2004 Constitutional ammendment, that consecrated the binding effect of the judicial precedent, through the introduction of the article 103-A in the Federal Constitution; and the binding judicial precedent constitutional requirements and its legal system, disciplined by the Law 11417/2006. We will study the possible problems in the tax law, due to the binding judicial precedent edition by the Federal Supreme Court. We will face the question of the tax levying before the recognition, by the abridgment above, of the total or partial unconstitutionality of the general and abstract rule that ground it, and the nullity of the general and abstract rule that is acknowledged before and after the tax auto imposition homologation. We will still verify the nº 8 binding judicial precedent and the tax levying, that are object of judicial and res judicata discussion. We will study the repercussion of the binding judicial precedent on the tax credit dividing in the hypotheses of certification of the unconstitutionality rule which was used to ground it, on the credit in installments and on the rule that disciplines the prescription and decadence terms. Finally, we will debate about the undue repetition possibility, its requirements and term in this study case and the nº 08 binding judicial precedent effects, regarding this institute and the res judicata